A prospective, randomized, placebo‐controlled study of inferior turbinate surgery. (2nd February 2018) - Harju, Teemu; Numminen, Jura; Kivekäs, Ilkka; Rautiainen, Markus
Abstract : Objectives/Hypothesis: The purpose of this study was to compare radiofrequency ablation, diode laser, and microdebrider‐assisted inferior turbinoplasty techniques in the treatment of chronic nasal obstruction caused by inferior turbinate enlargement, and to compare these techniques with a placebo procedure. Study Design: Prospective, randomized, single‐blinded, placebo‐controlled study. Methods: A total of 98 consecutive patients with enlarged inferior turbinates due to persistent year‐round rhinitis were randomized into a placebo, radiofrequency ablation, diode laser, and microdebrider‐assisted inferior turbinoplasty groups in a ratio of 1:2:2:2. All the procedures were carried out under local anesthesia with the patients' eyes covered. Assessments were conducted prior to surgery and 3 months subsequent to the surgery. Results: The severity of nasal obstruction measured by visual analog scale score decreased statistically significantly in all the groups, including placebo. Radiofrequency ablation ( P = .03), diode laser ( P = .02), and microdebrider‐assisted inferior turbinoplasty ( P = .04) all decreased the symptom score of the severity of nasal obstruction statistically significantly more compared to the placebo procedure. Conclusions: The placebo effect had a large role in the overall improvement of the severity of nasal obstruction after the inferior turbinate surgery. However, all three techniques provided a statistically significant additional reduction of the severity of nasal obstruction compared to the placebo procedure. Level of Evidence: 1b. Laryngoscope, 128:1997–2003, 2018